Affordability In Amortisation Of Public Urban Workforce Home Ownership In Sokoto, Nigeria - Alhaji, Hayatu (2010)
This research study is based purely on the home ownership of public urban workforce housing in Nigeria, with particular focus on affordability in amortisation. Kajian penyelidikan ialah rnengenai kajian tahap kernarnpuan pernilikan rurnah oleh tenaga kerja dalarn sektor awarn di bandar di Nigeria, dengan fokus utarna rnengena1 tahap kernampuan mereka dalarn rnelunaskan bayaran pinjarnan.